Development of transcranial sonothrombolysis as an alternative stroke therapy: incremental scientific advances toward overcoming substantial barriers. (March 2013) - Lapchak, Paul A; Kikuchi, Kiyoshi; Butte, Pramod; Hölscher, Thilo
Transcranial ultrasound and high intensity focused ultrasound technologies have been developed as a method of thrombolysis to be applied to the treatment of acute ischemic stroke. The originating idea to apply ultrasound to treat disease states dates back from the 1930s to 1940s when seminal research findings suggested that ultrasound could have an effect on biological systems and the brain, but the mechanism(s) involved in the effects were unknown. This exciting field of research has flourished since the potential exists to effectively utilize ultrasound to induce thrombolysis noninvasively or perhaps in combination with a thrombolytic agent, such as tissue plasminogen activator or secondary pharmaceutical such as microbubbles to promote cerebral reperfusion and clinical improvement. While there is great enthusiasm in this field of stroke treatment, specific parameters required for optimal sonothrombolysis such as output power, duty cycle, pulse width, and exposure time, as well as the impact of skull bone characteristics and flow mechanics, remain to be defined. This article analyzes relevant ultrasound studies to provide a synthesis of insight in the field of sonothrombolysis to attempt to provide direction for possible future use in stroke patients.